MUTATION OF NONASSOCIATIVE ALGEBRAS - Abdrashit, Almat; Mashurov, Farukh (Journal of Emerging Technologies and Computing, 2024)
We consider bicommutative algebras under mutationproducts. We obtain all identities of degree three of any bicommutative algebra under mutation product. Moreover, we prove that all identities in degree threeare consequences of two independent identities.